A CASE STUDY OF PRICE-LEVEL ADJUSTMENTS. - Corbin, Donald A. (The Accounting Review, 1955)
The article presents a case study of price-level adjustments to the financial reports of a large department store. The method outlined is designed for a study of a twenty-year period. The results of the adjustments to dollars of constant value revealed the expected distortions in periodic income reporting. In as much as the general price level rose during the year ended January 31, 1947, the adjusted balance sheet reveals that the non-monetary items, such as inventories, land, and depreciating assets, exceeded the historical costs by material amounts. In the proprietorship section, the value of the stockholders' original investments in common stock was increased by $6,368. The retained earnings are not as high as reported by $3,621, due to the continual overstatement of "real" income during the inflation years. The net income after taxes was distorted in the annual report by almost a half million dollars. In addition, an unrealized loss of $946 was omitted entirely from the report to stockholders. It appears that this type of information would have been very informative to existing and prospective stockholders.